Photocatalytic Hydrogenation of Alkenes Using Water as Both the Reductant and the Proton Source - Xinzhe Tian; Ming Qiu; Wankai An; Yun‐Lai Ren (Advanced Science)
Abstract Utilization of clean and low‐cost water as the reductant to enable hydrogenation of alkenes is highly attractive in green chemistry. However, this research subject is considerably challenging due to the sluggish kinetics of the water oxidation half‐reaction. It is also very difficult to avoid the undesired oxidation of alkenes because that this oxidation is far easier to occur than the desired oxidation of water from thermodynamic standpoint. Herein, this challenge is overcome by applying a cooperative catalysis where HCl is used as the cocatalyst to accelerate Pt/g‐C3N4‐catalyzed water oxidation and suppress the undesired oxidation of the alkene. This provides an example for using water as the reductant and the proton source to enable the photocatalytic hydrogenation of alkenes. The present method exhibits broad substrate applicability, and allows various arylethenes and aliphatic alkenes to undergo the hydrogenation smoothly.